Recreational Opportunities For Public Use in Ayer Hitam Forest: Setting the Stage and Park Management Approach - Mohd, Abdullah; Yaman, Amat Ramsa; Jamaluddin, Mohd Ariff (Universiti Putra Malaysia Press, 1999)
This paper discusses the concept of forest park for public recreational use and educational resource to be provided by Ayer Hitam Forest Reserve in Puchong, Selangor. This reserve has served as a teaching and research site but must be ready to allow people to set foot in. The recreation opportunity to be provided must be able to accommodate recreational needs that prioritised rewarding experience and educational-based recreation opportunity within the natural setting. Any recreational access and utilisation must involve low impact use and its development has to be based on the ecological limitation of the forest reserve. For a benefiting use of the area for recreation and its stewardship, the forest requires the practise of park recreation management and an integrated institutional arrangement. These include provision of recreational opportunities to the public albeit protection of the resources. In conclusion it is recommended that Ayer Hitam Forest Reserve be classified and gazetted as an open forest reserve.